Hadith #547 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We used to offer the Maghrib prayer with the Prophet (ﷺ) and after finishing the prayer one of us may go away and could still see as Par as the spots where one’s arrow might reach when shot by a bow.
Grade: Sahih

Hadith #2238 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We worked on farms more than anybody else in Medina. We used to rent the land at the yield of specific delimited portion of it to be given to the landlord. Sometimes the vegetation of that portion was affected by blights etc., while the rest remained safe and vice versa, so the Prophet (ﷺ) forbade this practice. At that time gold or silver were not used (for renting the land). If they provided the seeds, they would get so-and-so much.
Grade: Sahih

Hadith #2250 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
My uncle Zuhair said, “Allah’s Messenger (ﷺ) forbade us to do a thing which was a source of help to us.” I said, “Whatever Allah’s Messenger (ﷺ) said was right.” He said, “Allah’s Messenger (ﷺ) sent for me and asked, ‘What are you doing with your farms?’ I replied, ‘We give our farms on rent on the basis that we get the yield produced at the banks of the water streams (rivers) for the rent, or rent it for some Wasqs of barley and dates.’ Allah’s Messenger (ﷺ) sa
Grade: Sahih

Hadith #2389 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We used to offer the `Asr prayer with the Prophet (ﷺ) and slaughter a camel, the meat of which would be divided in ten parts. We would eat the cooked meat before sunset.
Grade: Sahih

Hadith #2612 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We used to work on the fields more than the other Ansar, and we used to rent the land (for the yield of a specific portion of it). But sometimes that portion or the rest of the land did not give any yield, so we were forbidden (by the Prophet (ﷺ) ) to follow such a system, but we were allowed to rent the land for money.
Grade: Sahih

Hadith #3128 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying, “Fever is from the heat of the (Hell) Fire; so cool it with water.”
Grade: Sahih

Hadith #5286 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
We were with the Prophet (ﷺ) in Dhul-Hulaifa and there the people were struck with severe hunger. Then we got camels and sheep as war booty (and slaughtered them). The Prophet (ﷺ) was behind all the people. The people hurried and fixed the cooking pots (for cooking) but the Prophet (ﷺ) came there and ordered that the cooking pots be turned upside down. Then he distributed the animals, regarding ten sheep as equal to one camel. One of the camels ran away and there were a few horses with the
Grade: Sahih

Hadith #5291 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
that he said, “O Allah’s Messenger (ﷺ)! We have no knife.” The Prophet (ﷺ) said, “if the killing tool causes blood to gush out, and if Allah’s Name is mentioned, eat (of the slaughtered animal). But do not slaughter with a nail or a tooth, for the nail is the knife of Ethiopians and a tooth is a bone.” Suddenly a camel ran away and it was stopped (with an arrow). The Prophet (ﷺ) then said, “Of these camels there are some which are as wild as wild beasts; so if one of them run
Grade: Sahih

Hadith #5294 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Eat what is slaughtered (with any instrument) that makes blood flow out, except what is slaughtered with a tooth or a nail.’
Grade: Sahih

Hadith #5297 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
I said, “O Allah’s Messenger (ﷺ)! We are going to face the enemy tomorrow and we do not have knives.” He said, “Hurry up (in killing the animal). If the killing tool causes blood to flow out, and if Allah’s Name is mentioned, eat (of the slaughtered animal). But do not slaughter with a tooth or a nail. I will tell you why: As for the tooth, it is a bone; and as for the nail, it is the knife of Ethiopians.” Then we got some camels and sheep as war booty, and one of those camels ran
Grade: Sahih

Hadith #5331 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
While we were with the Prophet. on a journey, one of the camels ran away. A man shot it with an arrow and stopped it. The Prophet (ﷺ) said, “Of these camels some are as wild as wild beasts, so if one of them runs away and you cannot catch it, then do like this (shoot it with an arrow).” I said, “O Allah’s Apostle! Sometimes when we are in battles or on a journey we want to slaughter (animals) but we have no knives.” He said, “Listen! If you slaughter the animal with anything that c
Grade: Sahih

Hadith #5504 - Sahih al-Bukhari - Rafi' bin Khadij bin Rafi' (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “Fever is from the heat of Hell, so abate fever with water.”
Grade: Sahih